“Arar Deshot Arai Pardesi”: The Rohingya crisis from the perspective of the host community - Masud Rana, Mohammad; Nashin, Taniya (The Jahangirnagar Review, 2024)
The Rohingya people are a stateless ethnic group who reside in the Rakhine state of western Myanmar. In order to escape from the military junta in Myanmar, many Rohingyas have taken refuge in Bangladesh. The government of Bangladesh, along with its local residents, has demonstrated humanitarianism by providing shelter to the Rohingyas. Despite the fact that six years have passed since the Rohingyas moved to Bangladesh in large numbers, there has been no visible progress in rehabilitating or repatriating them. This has caused a variety of problems for the local community. While there may be noticeable physical infrastructure development at the local level following the arrival of the Rohingya, closer inspection reveals that deforestation is taking place, and anxiety and insecurity at the local level are increasing day by day. Furthermore, due to the influx of Rohingyas, the local people are losing their culture and religious practices. They are even being forced to abandon their traditional occupations. For the locals, farming, fishing, and trekking in the mountains are, to some extent, no longer possible. As a result, the distance between the residents and the Rohingyas is gradually increasing, which is a cause for concern. Therefore, this research paper's primary objective is to shed light on the Rohingya crisis from the perspective of the host community, which has been directly impacted by the Rohingya influx. This article aims to provide an understanding of the issue from the perspective of the host community.